Anxiety as a predictor of the subjective quality of life - Jokić-Begić, Nataša (2004)
On the basis of population means, people's satisfaction with their own lives is within the range of 70-80 % of the measurement scale maximum score (%SM). According to the homeostatic model, the subjective quality of life (SQOL) is strongly influenced by the homeostatic system. Individuals who report a SQOL level which is less then 50 % SM can be considered to be experiencing the homeostatic failure. The aim of this study is to assess the subjective quality of life and to identify psychosocial predictors of SQOL among patients with a variety of gastroenterological diseases. 87 participants completed questionnaires measuring subjective quality of life, perceived social support, coping style, depression and anxiety. Mean level of SQOL is 73 %SM. Participants with a low level of subjective well-being (<50%) are more depressive (p<0.01), have higher levels of both trait and state anxiety (p<0.01), feel that they receive less social support (p<0.01), and use avoidance as a coping strategy more often than patients with the normal level of SQOL. Multiple regression analysis showed the trait-anxiety to be the most important factor in explaining lower subjective QOL. The group of patients remained within the normal range of subjective well-being expected by the homeostatic model. Gastroenterological disease alone does not result in a homeostatic failure. Psychological variables, especially the anxiety level, play the major role in maintaining the homeostatic balance. This finding suggests the importance and necessity of psychological support in treatment of physical illnesses.